Curcumin effects on blood lipid profile in a 6-month human study - Baum, Larry; Cheung, Stanley K.K.; Mok, Vincent C.T.; Lam, Linda C.W.; Leung, Vivian P.Y.; Hui, Elsie; Ng, Chelsia C.Y.; Chow, Moses; Ho, Ping C.; Lam, Sherry; Woo, Jean; Chiu, Helen F.K.; et al. (Pharmacological research, 2007)
Studies in animals and a short-term human study have suggested that curcumin, a polyphenolic compound concentrated in the curry spice turmeric, decreases serum cholesterol concentration. However, no controlled human trials have examined the effect of curcumin on cholesterol. This study investigated the effects of consuming curcumin on the serum lipid profile in men and women. Elderly subjects ( n = 36) consumed 4 g/d curcumin, 1 g/d curcumin, or placebo in a 6-month, randomized, double-blind trial. Plasma curcumin and its metabolites were measured at 1 month, and the serum lipid profile was measured at baseline, 1 month, and 6 months. The plasma curcumin concentration reached a mean of 490 nmol/L. The curcumin concentration was greater after capsule than powder administration. Consumption of either dose of curcumin did not significantly affect triacylglycerols, or total, LDL, and HDL cholesterol over 1 month or 6 months. However, the concentrations of plasma curcumin and serum cholesterol were positively and significantly correlated. Curcumin consumption does not appear to have a significant effect on the serum lipid profile, unless the absorbed concentration of curcumin is considered, in which case curcumin may modestly increase cholesterol.